From doll to deity: Assemblage & Transformation - Ahilan, P. (University of Jaffna, 2014)
This paper will focus on the unusual practice of transforming a doll into a goddess through the assemblage of body parts or organs using mixed media such as cloth, wood and metals and then infusing this doll-like figure with divinity. This process was documented at the Saivan Valavu Amman Kovil at Moolai. This kovil is located within private family land and only family members and close relatives come to worship at this shrine which does not contain an idol but rather, only two lighted lamps to signal the presence of the deity. These kinds of family temples are known as 'Pongal Kovils' because of their annual Pongal ceremony. This is the only day the Amman appears in figurative form through the temporary assemblage of doll-like body parts by a 'Satupadikkaran' who belongs to the Saivam or Pantaram caste. This paper will analyse this transformative act of assemblage using theories of peformativity and meaning making.